Strategi Respons Krisis pada Akun Tiktok @hulmofficial Berdasarkan SCCT dalam Kasus Black Campaign oleh Kompetitor - Ramadhani, Berliana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the viral one of the crises that has occurred on Tiktok, namely the black campaign carried out by a competing brand. Black campaign is the practice of deliberately spreading negative information to damage the public image, a person, product, or certain groups. In the end, the practice of black campaigns carried out by competitors results in a decrease in the reputation of the target company. Based on the Situational Crisis Communication Theory framework by Coombs, it is explained that dealing with existing crises is adjusted to the type of crisis that occurs. For this reason, this research analyzes the type of crisis and response strategies used by the Hulm brand in overcoming the crisis. This research uses a qualitative approach with a case study method with content analysis and documentation to find out in depth about the crisis that occurred on social media. The findings explain that the crisis that occurred between the Hulm brand and Brand X is categorized into the type of victim cluster crisis and the crisis response strategies used by the Hulm brand are deny, diminish, and bolstering.